Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.11628/ksppe.2022.25.6.585
|View full text |Cite
|
Sign up to set email alerts
|

Are Particulate Pollutants Emitted by Open-Burning of Agricultural Plastic Waste (Greenhouse LDPE Film) Harmful?

Abstract: Background and objective: Agricultural plastic waste (APW), which includes various types of plastics and greenhouse film, accounts for the largest volume of annual average incineration of plastic (Korea Environment Corporation, 2021). Open-burning incineration of such APW emits metallic particulate pollutants, the human hazard of which is widely known. As such, the systematic management of incinerable APW is required. Furthermore, basic physicochemical research on particulate pollutants (PPs) is needed for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…In particular, when it comes to Fe, it was reported that nanoparticles combined with oxygen and Fe at appropriate concentrations increased the yield of C3 plants (Li et al, 2021). A previous study (Kim and Lee, 2022) confirmed the effect of vegetation biofilters in underground stations on reducing Fe.…”
mentioning
confidence: 78%
“…In particular, when it comes to Fe, it was reported that nanoparticles combined with oxygen and Fe at appropriate concentrations increased the yield of C3 plants (Li et al, 2021). A previous study (Kim and Lee, 2022) confirmed the effect of vegetation biofilters in underground stations on reducing Fe.…”
mentioning
confidence: 78%